Pengaruh Perceived Quality dan Brand Familiarity Terhadap Brand Credibility (Studi Kasus Merek KFC) - Keke Tarisca; Lingga Yuliana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to examine the influence of perceived quality and familiarity on brand credibility on the KFC brand as a fast food provider. The quantitative research approach with purposive sampling as data collection so that 103 respondents were recorded, both female and male aged 17-47 years. Data were collected through the distribution of questionnaires with Google Form containing closed questions with a Likert scale as an alternative answer that represents respondents. Data were analyzed with Partial Least Square using SmartPLS. Thus, the test results showed that brand credibility was influenced by perceived quality, but not by brand familiarity.